Impact of Lymphocyte-Related Blood Parameters on Short- and Long-Term Outcomes of Patients Undergoing Thoracic Endovascular Aortic Repair. (November 2021) - Yang, Fan; Liu, Jitao; Chen, Lyufan; Fan, Ruixin; Zeng, Hongke; Geng, Qingshan; Luo, Jianfang
Lymphocyte-related blood parameters (LRBP), including neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio, and lymphocyte-monocyte ratio, could reflect a patient's overall inflammatory status. We aimed to clarify the association between preoperative LRBP and outcomes of type B aortic dissection (TBAD) patients undergoing thoracic endovascular aortic repair (TEVAR). A total of 841 patients were enrolled from 2010 to 2017. Twenty-six (3.1%) patients died during hospitalization and 71 (8.7%) patients died after a median follow-up of 47.3 months. Multivariate analyses showed that the NLR was the only independent predictor for in-hospital death (odds ratio, 1.15; 95% confidence interval [CI], 1.09-1.22; P < .001); 4.1 was identified as the optimum threshold for NLR after applying the X-tile program. Propensity score matching (PSM) was performed to diminish bias and yielded 174 matched pairs. Neutrophil-lymphocyte ratio >4.1 was demonstrated to be independently associated with follow-up mortality before (hazard ratio [HR], 2.53; 95% CI, 1.44-4.43; P = .001) and after PSM (HR, 3.11; 95% CI, 1.35-7.15; P = .008). The relationship between LRBP and follow-up reintervention or stroke were not significant ( P > .05 for both). Elevated NLR was an independent indicator for in-hospital and follow-up mortality in patients with TBAD undergoing TEVAR; this might provide additional risk stratification.